Health literacy in Italy: a cross-sectional study protocol to assess the health literacy level in a population-based sample, and to validate health literacy measures in the Italian language. Issue 11 (14th November 2017) - Lorini, Chiara; Santomauro, Francesca; Grazzini, Maddalena; Mantwill, Sarah; Vettori, Virginia; Lastrucci, Vieri; Bechini, Angela; Boccalini, Sara; Bussotti, Alessandro; Bonaccorsi, Guglielmo
Abstract : Introduction: Health literacy (HL) concerns the knowledge and competences necessary for people to meet complex health demands. The aims of this study are to assess the level of HL in a sample using the Italian version of the Newest Vital Sign and the association of HL and selected antecedents with health outcomes, and to develop and validate the Italian version of the three Brief Health Literacy Screeners, two subjective numeracy items and the short form and the short-short form of the European Health Literacy Survey Questionnaire. Methods and analysis: The study adopts a cross-sectional design and is being conducted in Florence, with information collected through telephone interviews. The population-based sample has been randomly selected using the registries of eight general practitioners (GPs). Based on a power calculation, 480 subjects will be included. Participants have been randomly offered two different questionnaires, each containing different HL measures. Data on sociodemographics and important antecedents and consequences of HL will be collected and the distribution of HL levels calculated. The mediating role of HL will be assessed using Preacher and Hayes' model. To assess the concurrent validity of the HL scales, correlation and receiver operating characteristic analyses will be performed. Ethics and dissemination: The study protocol has been approved by the Ethics Committee of the Area Vasta Centro. Results will be disseminated via scientific journals and conference presentations, and individual data made available to the GPs.